Delamination of carbon-fiber strengthening layer from concrete beam during deformation (infrared thermography) (Fracture and Structural Integrity, 2018)
Technology of strengthening reinforced concrete structures with composite materials has found wide application. The effectiveness of strengthening of concrete structures with externally bonded reinforcement is supported by a great deal of experimental evidence. However, the problem of serviceability of such structures has not been adequately explored. The present work describes the results of experimental studies on the loadcarrying capacity of concrete beams strengthened with carbon fiber reinforced plastic (CFRP). Special emphasis is placed on studying the debonding of the strengthening layer from the concrete surface and analyzing its influence on the load-carrying capacity of beams. Infrared thermography is used to detect the first signs of debonding and to assess the debond growth rate.
Keywords: Carbon fiber reinforced plastic; Reinforced concrete beams; Strengthening; Intermediate crack debonding; Infrared thermography; Quality control; Non-destructive testing methods